At What Levels of Financial Development Does Information Sharing Matter? - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
The purpose of this study is to investigate how increasing information sharing bureaus affect financial access. For this reason, we have employed contemporary and non-contemporary interactive Quantile Regressions in 53 African countries for the period 2004-2011. Information sharing bureaus are proxied with public credit registries and private credit offices. Financial development dynamics involving depth (at overall economic and financial system levels), efficiency (at banking and financial system levels), activity (from banking and financial system perspectives) and size are used. Two key findings are established. First, the effect of increasing private credit bureaus is not clearly noticeable on financial access, probably because private credit agencies are still to be established in many countries. Second, increasing public credit registries improves financial allocation efficiency and activity (or credit) between the 25th and 75th quartiles for the most part. As a main policy implication, countries in the top (or highest levels of financial development) and bottom (or lowest levels of financial development) ends of the financial efficiency and activity distributions are unlikely to benefit from enhanced financial allocation efficiency owing to increasing public credit registries.
Keywords: G20; G29; O16; O55; C52; 330; Information Sharing; Financial Development; Quantile Regression